2011
DOI: 10.1140/epja/i2011-11006-7
|View full text |Cite
|
Sign up to set email alerts
|

Blocking of coupling to the 02 + excitation in 154Gd by the [505]11/2- neutron in 155Gd

Abstract: [3][4][5][6][7] given for the existence of low-lying 0 + states in deformed actinide nuclei that did not have the properties of a β-vibration or of a pairing vibration.Evidence that the [505]11/2 − oblate orbital is associated with reduced pairing was first presented by J.D. Garrett et al. [8,9]. But a direct test of the underlying microscopic structure of |0 + 2 is required if we are to be completely confident in our interpretation of these states. a e-mail: jfss@tlabs.ac.za In many cases the single-particle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 36 publications
4
51
0
Order By: Relevance
“…Evidence indicating that the 0 2 + states in N = 88 and 90 nuclei are not β vibrations [6] but 2p-2h neutron states lowered into the pairing gap by configuration dependent pairing has been presented in Refs. [7,8]. It was argued that they are classic examples of "pairing isomers" [9] forming a "second vacuum" [7] on which a complete set of excited deformed states are built that are congruent to those built on the 0 1 + ground state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence indicating that the 0 2 + states in N = 88 and 90 nuclei are not β vibrations [6] but 2p-2h neutron states lowered into the pairing gap by configuration dependent pairing has been presented in Refs. [7,8]. It was argued that they are classic examples of "pairing isomers" [9] forming a "second vacuum" [7] on which a complete set of excited deformed states are built that are congruent to those built on the 0 1 + ground state.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8]. It was argued that they are classic examples of "pairing isomers" [9] forming a "second vacuum" [7] on which a complete set of excited deformed states are built that are congruent to those built on the 0 1 + ground state. Evidence for this [10] has also been found in 152 Sm.…”
Section: Introductionmentioning
confidence: 99%
“…18 can be interpreted as due to K mixing within the parent states of the 162 Er, 164 Er, [24,[35][36][37][38][39][40]. The horizontal axis is the ratio of the ground-state-band dynamic and kinematic moments of inertia.…”
Section: B 162 Ermentioning
confidence: 99%
“…This implies that |0 + 2 has a two-quasi-neutron configuration. In the following letter [53] it is shown that the odd neutron occupying the [505]11/2 − orbital in 155 Gd, blocks the coupling of this orbital to |0 + 2 . This determines the nature of the quasi-neutron configuration − orbital.…”
Section: (B)-(d)mentioning
confidence: 99%